RISKS OF THE INDUSTRY 4.0 AND THEIR INFLUENCE ON INDUSTRIAL ORGANIZATIONS - M. Kuznetsova (Вестник университета)
This article considers risks of the Industry 4.0. Main features of their influence on industrial organizations and national economy in general have marked out. The main directions of development of digital economy in Russia have designated. The summary risk matrix of the Industry 4.0 has created. Levels and subsystems of risk factors of industrialization influencing the modern industrial organizations have allocated. Need of formation of methods and instruments of identification, diagnostics and risk management of the Industry 4.0 within COSO has proved.